Remind Me Who I Am: Social Interaction Strategies for Maintaining the Threatened Self-Concept. (September 2014) - Slotter, Erica B.; Gardner, Wendi L.
After failure, individuals frequently turn to others for support. The current research examined the process through which individuals utilize interpersonal relationships to stabilize threatened self-views. We may seek support to reassure us with warmth and acceptance after a self-threat, or to provide support for threatened self-knowledge. We proposed that although both types of support are likely to repair the affective consequences of a self-threat, only interacting with others who can provide evidence from the individuals' past that reconfirms a threatened self-aspect would help stabilize the self-concept. Two studies demonstrated that, for individuals who have suffered a self-threat, receiving specific evidentiary support for the threatened self-aspect was more effective at restoring confidence in both the specific self-aspect and at recovering self-concept clarity than was receiving emotional support, whether the interaction was imagined (Study 1), or offered in person (Study 2) after the threat.